Medicine education through a Gender lens - Siri, Anna; Larentis, Omar; Ciliberti, Rosagemma (Medicina Historica, 2020)
A gender approach is a fundamental ethical and scientific commitment to ensure the best care for each person, respecting the differences, and thus achieving an effective personalized medicine. Italy is the first country in Europe to formalize the inclusion of the concept of "gender" in medical curricula, but the implementation is not the same across universities. Methodology Students (330) enrolled in the first year of the Medicine and Surgery course at the University of Genoa (a.y. 2019-20) were asked to answer a questionnaire on the relevance and usefulness of a gender dimension in medical education, consisting of five closed-ended questions as well as two one open-ended questions. Results The development of a gender approach is viewed very positively by 71.14% of the students. The majority of first-year students agree with a personalized view of medicine. The knowledge of gender medicine is also considered very useful within the educational programs by 82.84% of the students. However, the answers about which medical areas should benefit more from a gender approach reveal that students have still a superficial view of the subject. Only half of the students (52.73%) consider it useful to include a brief course on the history of gender medicine. Conclusion The findings show that future physicians are responsive to the value of a gender approach in medicine. Further studies are needed to investigate how such gender-oriented efforts should be outlined in medical training to be most effective, not forgetting taking into account the different gender approaches in different cultures and healing systems.